Drawing projects : an exploration of the language of drawing - Maslen, Mick.; Southern, Jack. (London : Black Dog, 2011)
Includes profiles and interviews of the following artists: Cornelia Parker, Jeff Koons, Julie Mehretu, Claude Heath, Martin Wilner, Charles Avery, Gemma Anderson, Tim Knowles, Mick Maslen, Jeanette Barnes, Kate Atkin, Benedict Carpenter, Dryden Goodwin, Shahzia Sikander, William Kentridge, Keith Tyson, Franziska Furter, Jake & Dinos Chapman.
boek